2021
DOI: 10.1017/s1368980021000823
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with obesity outcomes in adults: an umbrella review of systematic reviews

Abstract: Objective: The aim of this umbrella review was to summarize the evidence from existing systematic reviews on the association between different dietary patterns and overweight or obesity outcomes in adults. Design: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and searched the MEDLINE, EMBASE, CINAHL, Cochrane, Scopus, and Web of Science for systematic reviews reporting on dietary patterns and weight gain or overweight/obesity outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…One possible mechanism is that the consumption of this diet appears to be a marker of diet diversity. Another explanation is that rice and vegetables are considered to have a protective effect against obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that the consumption of this diet appears to be a marker of diet diversity. Another explanation is that rice and vegetables are considered to have a protective effect against obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy diet pattern has been associated with an increased risk of weight gain [44] or obesity [45,46]. By contrast, our recently published umbrella review of 16 systematic reviews showed that high adherence to the MDS was consistently associated with a decreased risk of obesity [12]. Previous research has shown that the nutrient-rich low-energy composition of the diet pattern defined using a high MDS [47] was associated with preventing weight gain in the long term [48].…”
Section: Main Findingmentioning
confidence: 98%
“…Lower quintiles are indicative of individuals living in areas with higher levels of disadvantage. For the MDS, we followed the method proposed by Tricopoulou et al [24], since it was one of the most common one reported in the published literature to assess adherence to the Mediterranean diet [12]. A value of 0 or 1 was given to nine components according to sex-specific medians.…”
Section: Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now a large body of evidence from over 20 systematic reviews and meta-analyses [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], published since 2000, of observational and intervention studies assessing diet and physical activity (PA) components associated with weight gain. These report that increased intake of diets characterized by high energy-dense discretionary foods and beverages are associated with weight gain [ 11 , 14 , 17 , 18 , 19 , 21 , 23 , 24 , 25 , 30 ] and limited consumption of discretionary foods and beverages, higher consumption of core foods (e.g., fruit, vegetables, whole grain or dietary fiber) and higher diet quality are associated with reduced weight gain in the adult population [ 10 , 12 , 13 , 15 , 16 , 20 , 22 , 26 , 27 , 28 , 29 , 31 ]. Evidence also consistently reports that moderate-to-vigorous intensity PA (≥150 min/week) is associated with lower weight gain [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%